Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T20:46:52+01:00
3(a+2b-3c)-2(a-2c)+5(c-b)-(a+b)= 3a+6b-9c-2a+4c+5c-5b-a-b=0
1/2a(a+1)-2(a²/4-a/2)=1/2a² + 1/2a - 1/2a²+a = 1 i 1/2 a
1/3a(a+1)-4(1/3a²-1/12a)-a(1-a)=1/3a² + 1/3a - 4/3a² +1/3a - a +a² = -1/3 a
0,2(5a+10b)-7(0,1a-b)+a-b= a + 2b - 0,7a +7b+a-b = 1,3a+8b
2010-01-04T21:09:42+01:00
1) 3(a+2b-3c)-2(a-2c)+5(c-b)-(a+b)=3a+6b-9c -2a+4c+5c-5b-a-b=-2a-2b

2) 1/2a(a+1)-2(a²/4-a/2)=(mnożymy to przez 4-żeby się pozbyć ułamka)=
2a(4a+4)-8(a[do kwadratu]-2a)=8a-8a-8a[kwadrat]+16a=-8a[kwadrat]+16a=(pierwiastkujemy)=-8a+(pierwiastek z)16a=-8a+4a=-4a

3) 1/3a(a+1)-4(1/3a²-1/12a)-a(1-a)=(mnozymy przez 12)=4a(12a+12)-48(4a<kwadrat>-a)-12a(12-12a)=48a(kwadrat)+48-192a(kwadrat)-48a-144a-144a(kwadrat)=-144a-288a(kwadrat)

4) 0,2(5a+10b)-7(0,1a-b)+a-b=a+2b+0,7a+7b+a-b=8b-0,7a

Proszę może choć troche pomogłam...;D